Interaction of antimicrobial peptide protegrin with biomembranes - Gidalevitz, David (National Academy of Sciences, 2003)
The antimicrobial peptide protegrin-1 (PG-1) interacts with membranes in a manner that strongly depends on membrane lipid composition. In this research we use an approach representing the outer layers of bacterial and red blood cell membranes with lipid monolayers and using a combination of insertion assay, epifluorescence microscopy, and surface x-ray scattering to gain a better understanding of antimicrobial peptide's mechanism of action. We find that PG-1 inserts readily into anionic dipalmitoyl-phosphatidylglycerol, palmitoyl-oleoyl-phosphatidylglycerol, and lipid A films, but significantly less so into zwitterionic dipalmitoyl-phosphatidylcholine, palmitoyl-oleoyl-phosphatidylcholine, and dipalmitoyl-phosphatidylethanolamine monolayers under similar experimental conditions. Epifluorescence microscopy shows that the insertion of PG-1 into the lipid layer results in the disordering of lipid packing; this disordering effect is corroborated by grazing incidence x-ray diffraction data. X-ray reflectivity measurements further point to the location of the peptide in the lipid matrix. In a pathologically relevant example we show that PG-1 completely destabilizes monolayer composed of lipid A, the major component in the outer membrane of Gram-negative bacteria, which is likely to be the mechanism by which PG-1 disrupts the outer membrane, thus allowing it to reach the target inner membrane.